Variabilitas Harian Equatorial Spread F di Atas Biak (01 oLS, 135 oBT) - Buldan Muslim; Sarmoko Saroso; The Houw Liong (Institut Teknologi Bandung, 2001)
The occurrence of equatorial spread F (ESF) at Biak BT) 01 oLS,135 oBT during March and April has been investigated on daily basis in sunspot medium years 1992 in terms of the growth rate of irregularities by the gravitational Rayleigh-Taylor (GRT) instability mechanism which includes the gravitational and cross-field instability terms. The occurrence statistics of ESF at Biak are examined in relation to maximum of h’F after sunset, rate of h’F and fluctuation of rise as well as with solar and magnetic activity conditions. It is found that the day-to-day variation of ESF occurrence at Biak can be accounted generally for on the basis of the GRT mechanism. On the basis of March data from 1992 – 1995 occurrence of ESF decrease with decreasing solar activity.